Pengaruh dukungan sosial dari orang tua terhadap motivasi belajar Mahasiswa komplasi Bima di kota Malang - Muhamad Rizkan; Dewanti Ruparin Diah; Al Thuba Septa Priyanggasari (University of Merdeka Malang, 2021)
This study aims to investigate the influence of social support for parents of students learning motivation Komplasi in Malang. The study population was all members of the Bima Komplasi student in Malang City. which numbered 134 students. Sampling in this study used simple random sampling technique and obtained 70 research samples from Komplasi Bima students. The results of data analysis that has been done with linear regression calculations obtained a value of 0,000. These results can be concluded that there is a positive influence between social support from parents and students' motivation to learn Komplasi Bima in Malang because the sig p value 0.05. Student motivation can not be increased if social support from parents is low and therefore it is expected that parents always give a sense of optimism and self-confidence to their children.